2010
DOI: 10.1093/nar/gkq824
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a G-quadruplex at the BCL2 major breakpoint region of the t(14;18) translocation in follicular lymphoma

Abstract: The t(14;18) translocation in follicular lymphoma is one of the most common chromosomal translocations. Most breaks on chromosome 18 are located at the 3′-UTR of the BCL2 gene and are mainly clustered in the major breakpoint region (MBR). Recently, we found that the BCL2 MBR has a non-B DNA character in genomic DNA. Here, we show that single-stranded DNA modeled from the template strand of the BCL2 MBR, forms secondary structures that migrate faster on native PAGE in the presence of potassium, due to the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
133
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 60 publications
5
133
1
Order By: Relevance
“…2B), even in the absence of KCl (bottom spectra). Imino proton resonances in the region 10-12 ppm have been assigned to guanine imino protons engaged in Hoogsteen base pairs within individual G quartets and are considered signatures of G quadruplex structure formation (Fürtig et al 2003;Menon et al 2008;Nambiar et al 2011). While DNA G quadruplexes require the presence of potassium ions for folding, RNA G quadruplexes of identical sequence can fold even in the absence of these ions, but have low stability (Joachimi et al 2009).…”
mentioning
confidence: 99%
“…2B), even in the absence of KCl (bottom spectra). Imino proton resonances in the region 10-12 ppm have been assigned to guanine imino protons engaged in Hoogsteen base pairs within individual G quartets and are considered signatures of G quadruplex structure formation (Fürtig et al 2003;Menon et al 2008;Nambiar et al 2011). While DNA G quadruplexes require the presence of potassium ions for folding, RNA G quadruplexes of identical sequence can fold even in the absence of these ions, but have low stability (Joachimi et al 2009).…”
mentioning
confidence: 99%
“…One of the major causes of genomic instability being actively investigated is the occurrence of non-B DNA in the genome (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Bioinformatic analyses have revealed the presence of several such non-B DNA structures throughout the genome (26,27).…”
mentioning
confidence: 99%
“…Gquadruplexes, which are four-stranded DNA molecules, are suggested to be present in the promoters of many genes and at the telomeres, thereby performing functions like gene regulation and chromosomal end protection (28)(29)(30)(31)(32)(33). Recent studies have also shown that altered DNA structures like cruciform and G-quadruplexes could play a significant role in the generation of chromosomal translocations in certain leukemias and lymphomas (15,18,20,(34)(35)(36)(37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies point out that BCL2 MBR adopts a non-B DNA structure in genomic DNA (Gquadruplex), which contributes to chromosomal fragility due to the single-stranded character at the region (Nambiar et al 2011;Zhao et al 2010). Moreover, the analysis of breakpoint junctions in lymphoma patients displayed that MBR breaks focused on three CpG peaks (Tsai et al 2008), suggesting that CpG sites are hotspot for breaks in MBR.…”
Section: Introductionmentioning
confidence: 99%